Intracordal auricular cartilage injection for unilateral vocal fold paralysis. Issue 1 (25th April 2014) - Lim, Yun‐Sung; Lee, Yoon Se; Lee, Jin‐Choon; Lee, Byung‐Joo; Wang, Soo‐Geun; Park, Hee‐June; Nam, Su‐Bong; Bae, Yong‐Chan
Abstract We evaluated the efficacy and outcome of intracordal auricular cartilage injection in patients with unilateral vocal fold paralysis. Our interest developed from findings of a canine model study that reported that histologic characteristics of cartilage were preserved 2 and 3 years after intracordal autologous cartilage injection. Between May 2002 and July 2010, 29 patients with breathy dysphonia caused by unilateral vocal fold paralysis underwent intracordal auricular cartilage injection. Each subject underwent preoperative and postoperative perceptual assessments, acoustical voice analysis, and videostroboscopy. Fourteen patients were male, and the mean age was 52‐years old. Patients were tracked for a mean duration of 257 days. Injections were performed through a transoral approach under general anesthesia. Perceptual assessments by GRBAS scale, acoustic parameters of jitter, shimmer, noise‐to‐harmonic ratio, and maximum phonation time significantly improved at 3, 6, and 12 months after cartilage injection (p < 0.005). No major complications were observed after injection. Initial clinical results with intracordal auricular cartilage injection are promising for patients with unilateral vocal fold paralysis. Autologous auricular cartilage can be a safe, effective, and alternative material for vocal fold medialization, and can be a long lasting one. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 47–51, 2015.